Flagellin-dependent TLR5/caveolin-1 as a promising immune activator in immunosenescence - Lim, Jae Sung (Aging Cell, 2015)
The age-associated decline of immune responses causes high susceptibility to infections and reduced vaccine efficacy in the elderly. However, the mechanisms underlying age-related deficits are unclear. Here, we found that the expression and signaling of flagellin (FlaB)-dependent Toll-like receptor 5 (TLR5), unlike the other TLRs, were well maintained in old macrophages, similar to young macrophages. The expression and activation of TLR5/MyD88, but not TLR4, were sensitively regulated by the upregulation of caveolin-1 in old macrophages through direct interaction. This interaction was also confirmed using macrophages from caveolin-1 or MyD88 knockout mice. Because TLR5 and caveolin-1 were well expressed in major old tissues including lung, skin, intestine, and spleen, we analyzed in vivo immune responses via a vaccine platform with FlaB as a mucosal adjuvant for the pneumococcal surface protein A (PspA) against Streptococcus pneumoniae infection in young and aged mice. The FlaB-PspA fusion protein induced a significantly higher level of PspA-specific IgG and IgA responses and demonstrated a high protective efficacy against a lethal challenge with live S. pneumoniae in aged mice. These results suggest that caveolin-1/TLR5 signaling plays a key role in age-associated innate immune responses and that FlaB-PspA stimulation of TLR5 may be a new strategy for a mucosal vaccine adjuvant against pneumococcal infection in the elderly.